Rancang Bangun Alat Tekuk Pembuat Begel Portabel Dan Perbandingan Kecepatan Produksinya Dengan Alat Tradisionil - Zulhendri Zulhendri; Yuliarman Yuliarman; Aidil Zamri; Asmed Asmed; Nota Effiandi (Politeknik Negeri Padang, 2023)
Begel or sekang is a longitudinal reinforcing ring to hold the shear stress that occurs in a concrete column or pillar, the putel is placed so that each longitudinal reinforcement is held so as not to bend out. So far, begel are made by sticking a shaft iron into a wood and then begel the iron manually, until it is obtained as needed. Traditional bending tools like this are inefficient because they require more energy to bend them and cannot be carried. Therefore it was designed and made PORTABLE BEGEL MAKING BENDING TOOLS. To test the speed of this tool compared with traditional bending tools. From the results of statistical tests it was concluded that the portable buckle making buckle tool is faster than the traditional buckling tool. This portable buckling device is designed more simply so that it can be carried anywhere and is easily made by construction workers.